Branched Thiophene Oligomer/Polymer Bulk Heterojunction Organic Solar Cell. Issue 1737 (28th May 2015) - Martinez, Francisco; Neculqueo, Gloria; Vasquez, Sergio O.; Lemmetyinen, Helge; Efimov, Alexander; Vivo, Paola
ABSTRACT: Thiophene small novel branched structures have been proposed as candidates for dopant agents transporting holes-electron in organic solar cell (OSC). Low-band gap of these branched oligotiophene have been obtained to be used in organic solar cells. Two branched thiophene oligomers, a sexithienylene vinylene (E)-Bis-1, 2-(5, 5´´-Dimethyl-(2, 2´:3´, 2´´-terthiophene) vinylene, (BSTV) and octathienylene vinylene (BOTV) (E)-Bis-1, 2-(5, 5´´´-Dimethyl-(2, 2´:5´, 2´´:3´, 2´´´-tetrathiophene) vinylene oligomers, have been synthesized and used as electron donor or dopant in a bulk heterojunction poly(3-hexylthiophene) (P3HT), /[6, 6]-phenyl C61-butyric acid methylester (PCBM), Organic Photovoltaic cell.